Barium titanate screen-printed thick films - Stojanovic, B. D.; Foschini, C. R.; Pavlovic, V. B.; Pavlovic, V. M.; Pejovic, V; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
Barium titanate (BT) thick films were prepared from mechanically activated powders based on BaCO(3) and TiO(2). After homogenization and milling in a high-energy vibro mill, the powders were calcined at 700 degreesC for 2 h by slow heating and cooling rates. A thick film paste was prepared by mixing BT fine powders with small amount of low temperature sintering aid and organic binder. The thick films were screen-printed on alumina substrates electroded with Ag-Pd. The BT films were sintered at 850 degreesC for 1 h. The thickness was 25-75 mum depending of number of layers. The microstructure of thick films and the compatibility between BT layers and substrate were investigated by SEM Results of dielectric property measurements are also reported. (C) 2002 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: films; dielectric properties; BaTiO(3) and titanates; multilayer ceramic capacitors